Estudo do comportamento mecânico e microestrutural da superliga inconel 718 após tratamento térmico de duplo envelhecimento - Resende, Fabricia Assis [UNIFESP] (2015)
The aim of this work was the study of the double aging heat treatment on the creep behavior of superalloy Inconel 718 comparing on the alloy without treatment (homogenized). The heat treatment was double aging, following the steps of solubilization (1095 °C during 1 hour) and double aging treatment (955 °C/1 h ? 720 °C/8h + 620 °C/8 h). The objective of this work was increase the mechanical resistance in creep of superalloy Inconel 718 by precipitation hardening phases, such as phases ?' (Ni3Al) and ?? (Ni3Nb) formed during the aging treatment. The creep tests were carried out at constant load mode and constant temperature (650 °C, 675 °C and 700 °C). The range of stress was determined by hot tensile test, ranging from 300 MPa to 625 MPa, both the temperature values and stress were chosen for the most severe operating conditions of its main application (gas turbines). The characterization techniques used in this study were scanning electron microscopy (SEM) for analysis microstructural and fractograpy; X-ray diffraction and Vickers hardness. The results indicate that the double aging samples presented higher mechanical strength. The hardness measurements for the double aging samples showed an increasing of 94.7% compared on the homogenized samples. The hot tensile test increased 17.1% of yield stress at 650 °C for double aging. The alloys treated with double aging also demonstrated increase on creep resistance. At 700 °C and stress of 510 MPa occurred an increasing of 72.7% over the creep lifetime of the material and reduction of 58.2% in elongation of the double aging sample. Stress exponent values were from of 4.7 to 5.6 for the homogenized alloy and 4.3 to 7.2 for the double aging. The creep values for activation energy were of 234.3 kJ/mol to 285 kJ/mol. These parameters suggest that creep mechanism is the climb dislocation mechanism. The results indicated that the samples that suffered double aging heat treatment showed greater resistance to deformation, showing that double aging treatment increased the superalloy mechanical strength.